SIMSPIRE: A Simulator of the Respiratory System - Andrea Bombarda; Silvia Bonfanti; Angelo Gargantini; Elvinia Riccobene (IEEE Access, 2025)
This paper introduces SIMSPIRE, a comprehensive simulator of the human respiratory system designed as a versatile tool for simulating various patient conditions. It can be used to model patients with a wide range of physiological traits, such as varying lung compliance and resistance, as well as respiratory conditions, such as chronic obstructive pulmonary disease (COPD) and acute respiratory distress syndrome (ARDS). The versatility of SIMSPIRE makes it suitable for simulating diverse respiratory scenarios and evaluating new algorithms or control strategies for ventilatory support. For this work, we have tested and evaluated our simulator by connecting as input the control software of a ventilator prototype. SIMSPIRE represents a significant advancement in the field of respiratory simulation. It provides a highly accurate and customizable platform for improving the design of ventilation systems and optimizing patient outcomes. By eliminating the need for expensive hardware simulators, SIMSPIRE has the potential to accelerate innovation and contribute to enhanced patient care in critical care settings.